种改进的基于PLC网络通信的长距离皮带输送系统 (2019)
种改进的基于PLC网络通信的长距离皮带输送系统，包括矿山运输PLC系统，其特征在于：所述电气室ER18 PLC系统处理器为西门子S7-400PLC；所述电气室ER18、ER17、ER16、ER15、ER14、ER13、ER12、ER11、ER10的触摸屏通过多模光缆将9个触摸屏连接成个冗余环形网络；在电气室ER18PLC上设置个PLC通讯模块实现与PLC系统网络的通讯；在每个电气室PLC上各设置台以太网交换机；用以太网网线将触摸屏和以太网交换机进行连接构成个冗余环形以太网通讯网络。本发明具有使全线皮带机连续运行和电气室ER11和ER10触摸屏连接到通讯网络上的优点。 The invention discloses an improved long-distance belt conveying system based on PLC network communication. The system comprises a mine transport PLC system, and is characterized in that a PLC system processor of an electrical room ER18 is a Siemens S7-400PLC; nine touch screens of the electrical room and electrical rooms ER18, ER17, ER16, ER15, ER14, ER13, ER12, ER11 and ER 10 are connected through a multimode optical cable to form a redundancy loop network; a PLC communication module is arranged on the PLC of the electrical room ER18 so as to realize communication with a PLC system network; the PLC of each electrical room is provided with an Ethernet switch; and the touch screens and the Ethernet switches are connected by use